PENGARUH VARIASI KOMPOSISI SERAT SABUT KELAPA TERHADAP KEKUATAN MEKANIK BAHAN GENTENG KOMPOSIT POLIMER - Milawarni Milawarni (Portal: Jurnal Teknik Sipil, 2013)
The research on the manufacture and characterization of polymer composite tile utilized the waste of polypropylene (PP) and coconut fiber (SSK) has been done. Asphalt material used is 10%, 10% PP and compositional variations of sand and SSK are (80:0), (79:1), (78:2), (77:3), (76:4) and (75:5). To find out the characterization of polymer composite tile, the mechanical are done. In the mechanical testing that includes testing the maximum tensite, flexural strength testing and impact is on the composition of the sample 4 (77:3) by 53.26 kgf/cm2 133.39 kgf/cm2 or 13.08 MPa and 2.00 J/cm2. The addition of coconut fiber is as much as 3% can increase the mechanical stength polymer composite tile.